PENYULUHAN NUTRISI SEIMBANG PADA IBU HAMIL RISIKO TINGGI BERBASIS KELUARGA - Hardaniyati; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha (Jurnal LENTERA, 2026)
Pregnant women require more nutrients than when they are not pregnant. This is because the nutrients consumed are for both the mother and the fetus. The fetus grows by absorbing nutrients from the mother's food intake and from the mother's own reserves. The goal of this community service is to increase pregnant women's knowledge about balanced nutrition for high-risk pregnancies as an early detection and prevention measure for high-risk pregnancies, thereby reducing mortality rates. The method used in this community service is to provide counseling on balanced nutrition for pregnant women, which was carried out in the working area of ​​the Labuapi Community Health Center, Labuapi District, West Lombok Regency, with a total of 30 pregnant women participating. Based on the results of the pre-test and post-test conducted, the results showed an increase in knowledge and understanding of mothers about Balanced Nutrition during pregnancy. It is hoped that there will be changes in the behavior of pregnant women in caring for their pregnancies so that pregnancy complications can be detected earlier and nutrition during pregnancy can be improved.